The influence of German on the English lexicon in the 20th century: an overview of the manifold subject areas and spheres of life enriched by German in the recent past - Landmann, Julia (English today, 2016)
While there is a multitude of studies on the influence English has exerted on German, the converse language contact scenario has been comparatively neglected. German borrowings which have recently been assumed into English have as yet received little attention in current research. The present paper intends to shed light on the impact of German on the English vocabulary in the 20th century. The various German words and meanings taken over into English in the last few decades will be divided into manifold subject areas in order to give a rounded picture of the different domains and spheres of life enriched by German in the recent past.